Reversible severe fatty liver induced by capecitabine: A case report. Issue 46 (November 2017) - Jiang, Yiyan; He, Qiancheng; Li, Suxia; Shi, Chang; Yang, Xiaolei
Abstract: Rationale: Capecitabine (CAP) is a chemotherapeutic agent used to treat breast and gastrointestinal cancers. The most common adverse reactions of CAP primarily included gastrointestinal and dermatological effects. Whereas, the CAP-induced fatty liver had never been reported. Patient concerns: In this study, a-69-year old female presented a history of hypertension with regulated blood pressure, whereas diabetes mellitus, hyperlipidemia, and hepatitis were excluded. No alcohol, tobacco, or other drugs use was declared. Diagnoses: She was diagnosed as infiltrating ductal carcinoma of left breast with the hepatic and pulmonary metastasis. The dihydropyrimidine dehydrogenase (DPD) deficiency is not involved. Interventions: She received treatment with CAP that was administered orally at a dosage of 1500mg twice daily intermittently (2weeks on/1 week off). The treatment was well-tolerated any typical adverse reactions such as diarrhea, nausea, and hand-foot syndrome (HFS) were noted. The parameters of the functional liver, the total cholesterol, and triglyceride were in normal ranges before and after therapy. After 3 cycles of the treatment, computed tomography (CT) scan revealed signs of fatty liver. After a 10-cycle course, CAP was substituted with tamoxifen because of the further aggravation of fatty liver. Outcomes: Several months after withdrawal, the follow-up CT scans demonstrated significant improvement of fatty liver. Lessons: We presented a case of breast cancer with severe fatty liver as a consequence of the administration of CAP that was not involved in DPD deficiency or CAP-associated hypertriglyceridemia; these potential adverse effects of therapy with CAP should be intensely investigated.